The Role of Digital Marketing in Moderating the Influence of Customer Experience, Product Quality, and Perceived Value on Repurchase Intention - Darwin Tantowi; Virdi Gunawan; Nasrani Septin Kristiani Gulo; Rinintha Parameswari (LPPM Universitas Buddhi Dharma, 2025)
Digital transformation has significantly changed the marketing landscape and consumer behavior, particularly in the context of repeat purchases. This study aims to examine the influence of Customer Experience, Product Quality, and Perceived Value on Repurchase Intention, and analyze the role of Digital Marketing as a moderating variable in this relationship. Data were collected through an online survey of 150 respondents who had made digital transactions and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that Product Quality and Digital Marketing have a significant positive effect on Repurchase Intention, while Customer Experience and Perceived Value do not show a significant effect. Furthermore, Digital Marketing does not moderate the relationship between the three independent variables and repurchase intention. These findings emphasize the importance of product quality and a strong digital marketing strategy in building customer loyalty, but also indicate that digital interventions have not been sufficient to strengthen the influence of customer experience and perceived value on repeat purchase decisions.